IDENTIFIKASI TINGKAT PENCEMARAN UDARA AKIBAT AKTIVITAS TRANSPORTASI - Djen, AYN Terto; Costa, Don Gaspar N. Da (FSTPT Indonesia, 2015)
Growth in the number of motor vehicles have an impact onthe increase involume, which in turn result in increased levels of pollutants resulting from the combustion engine of the motor vehicle. Congested corridors traffic rightly evaluated the air contaminant levels, so that the causesand/ortriggersand the potential negative impact of contaminants/pollutantsreferred to can be managed fruitfully. Prediction of pollutant levelsa nalogously performe dusing a variety of mathematical models that exist,where the preamble which can be used merely parameters based on the amount of traffic volume alone. Survey results showed that the volume of traffic on the roads Jl. Sudirmanis high so that the results of the simulation identified that CO, NOx and Pb are the types of pollutants whose levels have exceeded the threshold of airquality standards as required by the Minister of Environment Decree No.554/MENLH/10/1997 about the Pollutant Standards Index (ISPU) and as required under Indonesian Government Regulation No:.41/1999 on Ambient Air Quality Standards. Recommendation strategy and/or management technique is to 1) Control of pollutants in pollutant source by limiting the volume of vehicles disparsilocation-based activity, routine vehicle controll and vehicle operating restrictions of old-engined 2) Control of pollutants in the receiving contamination by limiting the duration of activity of the cur band/orusea mask covering the nose 3) environmental quality control at contaminated locations via a coveredyard of land all ocation policy (ban concrete floor) and road side vegetation 4) Vehicle Inspection and Maintenance 5) follow policies that ban covered parking area wih concrete and road side vegetation program.